2023
DOI: 10.1002/mabi.202300198
|View full text |Cite
|
Sign up to set email alerts
|

A Mucin‐Based Bio‐Ink for 3D Printing of Objects with Anti‐Biofouling Properties

Abstract: With its potential to revolutionize the field of personalized medicine by producing customized medical devices and constructs for tissue engineering at low costs, 3D printing has emerged as a highly promising technology. Recent advancements have sparked increasing interest in the printing of biopolymeric hydrogels. However, owing to the limited printability of those soft materials, the lack of variability in available bio‐inks remains a major challenge. In this study, a novel bio‐ink is developed based on func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…Laponite's bactericidal action is due to bacteria aggregation (limited to Gram-negative bacteria as Laponite did not cause flocculation of Gram-positive Bacillus subtilis bacteria nor did it bind to lipoteichoic acid from bacterial envelopes) [ 75 ]. Finally, regarding tissue engineering and scaffolding, although Laponite helps, the limited printability of the soft materials remains a challenge [ 172 ]. As regards intraocular administration, although no explicit references to limitations were found, intravitreal injection was reported to produce a transient IOP increase at around 3 days, similar to other hydrogels [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Laponite's bactericidal action is due to bacteria aggregation (limited to Gram-negative bacteria as Laponite did not cause flocculation of Gram-positive Bacillus subtilis bacteria nor did it bind to lipoteichoic acid from bacterial envelopes) [ 75 ]. Finally, regarding tissue engineering and scaffolding, although Laponite helps, the limited printability of the soft materials remains a challenge [ 172 ]. As regards intraocular administration, although no explicit references to limitations were found, intravitreal injection was reported to produce a transient IOP increase at around 3 days, similar to other hydrogels [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…To obtain mucins that can form a gel at neutral pH (when exposed to UV light in the presence of a photo initiator), bovine submaxillary mucin (BSM, Sigma‐Aldrich) was modified with methacrylic anhydride (MA, Sigma‐Aldrich) according to an adapted version of the protocol described by Rickert et al [ 30 ] BSM was selected since it is reported to be the commercially available mucin source closest to the human mucin MUC5B. [ 31 ] This constitutes the dominant mucin species in the human lung expressed by secretory cells in submucosal glands and in the superficial airway epithelium.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study, mucin has been used to 3D print objects with antibiofouling properties. 14 In recent times, mucin has emerged as a promising hydrogel material in diverse fields such as drug delivery, 15−17 cosmetics, 18,19 and wound healing, 20−22 showcasing its potential for innovative biomedical advancements. However, the inherent bonds of mucin alone are insufficient for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…These regions play a crucial role in modulating the growth and proliferation of cells . These glycosylated proteins also protect the tissues from infections due to their barrier properties and thus have been used as an antibiofouling material. This inherent antibiofouling property affords them a competitive advantage over other biopolymers. In a recent study, mucin has been used to 3D print objects with antibiofouling properties …”
Section: Introductionmentioning
confidence: 99%